Rahway, N.J., Rev. Code tit. 28, § 209 (1896) - (:unkn) unknown (My University, 1896)
That if any person between the hours of five P. M. and seven A. M. of any day, kindle or cause to be kindled, within the limits of the city, any bonfire or shall at any time of day or night fire or discharge within said city limits without written permission from the Mayor of the city, any cannon, gun, pistol or other firearms (except upon private property and premises of the party so discharging said firearms)the person so offending shall forfeit and pay for each and every such offense the sum of five dollars besides cost of conviction.
Keywords: DISCHARGE